Cross-sector collaboration in Oregon's forest sector: insights from owners and CEOs. (3rd April 2021) - Guerrero, Jose E.; Hansen, Eric
ABSTRACT: Cross-sector collaboration is emphasized as a means for forest sector companies to remain competitive in a global marketplace that is evolving toward greater use of bio-based products (bioeconomy). Nevertheless, questions remain regarding how companies can identify and develop innovations via cross-sector collaboration. This study addresses the potential of Oregon forest sector companies to collaborate with other sectors. Results show interest in collaboration among leaders of Oregon companies, given expectations of knowledge acquisition, increased capacity for innovation, and enhanced profitability. However, leaders describe a hesitancy within their companies as well as a host of changes that must take place before collaboration is likely. Suggestions include generational changes of leadership, more specialized employees, and building trust with potential partners. A traditional, conservative industry/company culture was the key barrier to collaboration. Despite opportunities promised by cross-sector collaboration, considerable development within companies is likely needed before cross-sector collaboration opportunities can be capitalized on.